SPATIAL ANALYSIS OF DENGUE HEMORRHAGIC FEVER CASES IN RELATION TO POPULATION DENSITY IN BANDAR LAMPUNG CITY - Ramayudha, Kurnia; Perdana, Agung Aji; Sari, Nurhalina; Nuryani, Dina Dwi (HEARTY, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health burden in Indonesia, particularly in densely populated urban areas. Bandar Lampung City is classified as an endemic region, with fluctuating case numbers each year. This study aims to analyze the relationship between population density and the distribution of DHF cases using a spatial analysis approach. A cross-sectional ecological design was employed. Secondary data were obtained from the Lampung Provincial Health Office regarding DHF cases and from the Central Bureau of Statistics regarding population density. The analysis involved Pearson’s correlation test to examine the association between population density and case numbers, as well as spatial mapping using QGIS 3.4.11 to illustrate distribution patterns. The findings revealed that DHF cases occurred not only in highly populated areas but also in subdistricts with moderate population density, particularly where the larva-free index (LFI) was low. Correlation tests demonstrated a significant negative relationship in 2022 (r = –0.341; p = 0.049) and 2023 (r = –0.327; p = 0.043), while the result for 2021 was not statistically significant (r = –0.276; p = 0.061). This study concludes that population density is not the primary determinant of DHF incidence. Environmental conditions, sanitation, and community behavior appear to play a more substantial role in disease transmission within Bandar Lampung City.